2011
DOI: 10.1007/s00167-011-1565-2
|View full text |Cite
|
Sign up to set email alerts
|

Why perform an ACL augmentation?

Abstract: This study provides a detailed justification in preserving ACL remnants and their vital role in surgical reconstruction of partial anterior cruciate ligament tears.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
35
0
6

Year Published

2013
2013
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(41 citation statements)
references
References 38 publications
0
35
0
6
Order By: Relevance
“…Surgically speaking, the interest in preserving the intact bundle is beneficial for several reasons, all described in the literature [54]:…”
Section: Partial Reconstructionsmentioning
confidence: 99%
“…Surgically speaking, the interest in preserving the intact bundle is beneficial for several reasons, all described in the literature [54]:…”
Section: Partial Reconstructionsmentioning
confidence: 99%
“…The proportion of isolated bundle tears in the knees undergoing ACL reconstruction was only 7% in this study, and an isolated PL bundle tear was detected in only one (0.6 %) of 156 knees. Surgical reconstruction might be required in symptomatic patients with partial ACL tears [13,21,33], and some surgeons prefer an ACL augmentation technique when treating the patients with partial ACL tears [4,5,33]. However, our study found that most remnant bundles are often loose and nonfunctional, even if the ACL remnant bridges the femur and the tibia [3].…”
Section: Discussionmentioning
confidence: 67%
“…The definition of remnant-preserving ACLR surgery is controversial because it currently refers to the following three major procedures: selective bundle augmentation (SBA) ACLR in a partial lesion, involving either the posterolateral or anteromedial bundle with functional remaining fibers; augmentation (AG) ACLR in a partial lesion, involving one or both bundles with some remaining functional tissue; and ACLR in a complete lesion, involving both bundles with some remaining nonfunctional tissue (NFRP-nonfunctional remnant preservation) [51][52][53][54][55][56]57 Partial ACL tears are frequent (5 %-38 %) [62•], and the remnant fibers have been given more importance in recent years. ACLR using a remnant-preserving technique also called ACL augmentation supposedly improves the ligamentization process, since the remnant functional fibers may biomechanically protect the graft, the vascularized remnant synovial envelope may enhance vascularization, and the valve mechanism created by the remaining tissue and the tunnel may inhibit the entry of synovial fluid, resulting in less tunnel enlargement; also, histological studies have shown mechanoreceptors in the remaining tissue that may optimize proprioceptive function [52, 54, 55, 57••, 58, 59•, 62•, 63••, 64,65].…”
Section: Remnant-preserving Aclrmentioning
confidence: 99%
“…Regarding the three types of remnant-preserving ACL surgeries, SBA is believed to provide better knee stability results, followed by AG and, lastly, by NFRP [51][52][53][54][55][56]57 Tunnel enlargement is caused by high levels of cytokines and inflammatory agents in the postsurgery synovial fluid bathing the tunnel graft-bone interface and micro-motion in this environment; also, tunnel enlargement is more common in the tibia consequent to gravity. Although a correlation between tunnel enlargement and clinical outcomes has not been conclusively demonstrated, it remains a concern in revision surgery.…”
Section: Remnant-preserving Aclrmentioning
confidence: 99%